Improved visualisation of hepatic metastases in gadoxetate disodium-enhanced MRI: Potential of contrast-optimised (phase-sensitive) inversion recovery imaging. - Ute Lina Fahlenkamp; Günther Engel; Lisa Christine Adams; Sarah Maria Böker; Minh Huynh Anh; Moritz Wagner; Bernd Hamm; Marcus Richard Makowski (PLoS ONE, 2019)
BACKGROUND:Detection of metastases can have a significant impact on therapy. Nevertheless, even in gadoxetate disodium-enhanced MR scans, very small hepatic metastases may be difficult to see. PURPOSE:To investigate the potential of a contrast-optimised (phase-sensitive) inversion recovery MR sequence in gadoxetate disodium-enhanced scans for detection of hepatic metastases. MATERIALS AND METHODS:With institutional review board approval and after written informed consent, 40 patients (18 male, 22 female) with suspected or known hepatic metastases were examined on a 1.5 T MR system. A T1-weighted gradient-echo volumetric-interpolated-breath-hold (VIBE) sequence was acquired as part of the standard imaging protocol 20 minutes after administration of gadoxetate disodium. Additionally, an IR sequence was acquired with an inversion time to suppress native signal from metastases. Overall image quality and delineation of lesions were assessed on VIBE as well as on magnitude-reconstructed (MAG) and phase-sensitive IR (PSIR) sequences. Lesion-to-liver contrast (LLC) was compared between VIBE and MAG images. RESULTS:Overall image quality was high in both VIBE and MAG IR sequences (VIBE 4.275; MAG 4.313), yet significantly lower in PSIR (4.038). Subjective delineation of lesions was higher on MAG and PSIR images compared to VIBE in all size groups with an overall statistically significant difference for VIBE vs. MAG vs. PSIR (p < .001) in the variance analysis. Mean LLC was 0.35±0.01 for VIBE sequences, and 0.73±0.01 for MAG. CONCLUSION:Contrast-optimised PSIR seems to improve imaging characteristics of hepatic metastases in gadoxetate disodium-enhanced scans compared to T1 gradient-echo VIBE sequences.